Development of novel hollow fiber membranes for forward osmosis applications - Laurentia E. K. Setiawan (2012)
Forward osmosis (FO) process has been gaining popularity in recent years as a potential alternative to pressure-driven membrane processes such as reverse osmosis (RO) for water desalination and wastewater reclamation. However, the main drawback of FO system is permeate flux decline due to internal concentration polarization (ICP) when conventional RO membranes are used. The only commercially available FO flat sheet membrane developed by Hydration Technologies Inc (HTI) presented low water permeation flux. Therefore, the development of novel FO membranes with optimized structure to reduce ICP has become a critical issue to facilitate FO practical applications. In this study, single layer asymmetric microporous hollow fiber membranes were fabricated using Torlon polyamide-imide (PAI) material as the porous support followed by a simple polyelectrolyte cross-linking using polyethyleneimine (PEI) to produce hollow fiber membranes with a positively charged nanofiltration (NF)-like selective layer. The newly developed PAI hollow fiber membranes show a pure water permeability of 2.19-2.25 l/m2.h.bar and reasonable NaCl and MgCl2 rejections of 49% and 94% at 1 bar, respectively. It is also found that in FO processes, when using 0.5 M MgCl2 as a draw solution and de-ionized (DI) water as the feed in the active layer facing feed water (AL-FW) configuration at 23C, the water fluxes of two PAI FO hollow fiber membranes are 8.36 and 9.74 l/m2.h, respectively, and the salt to water flux ratio (Js/Jv) of the two membranes is smaller than 0.4 g/l, which is lower than the data of 0.85 g/l for commercial HTI FO membrane. Different from a neutral membrane, the positively charged FO membrane provides double electric repulsions to the salt transfer through the membrane in the AL-FW configuration, leading to a reduction of salt penetration, while in the active layer facing draw solution (AL-DS) configuration, the positive charges facilitate salt transportation. This study provides a simple and effective approach to make hollow fibers with a NF-like skin suitable for FO applications. An improvement for the single layer PAI hollow fiber membranes has been carried out by incorporating a negatively charged polyelectrolyte layer on the selective skin, aiming to enhance membrane antifouling property. This new type of PAI FO membrane possesses pure water permeability of 3.7-4.3 l/m2.h.bar and Na2SO4 rejection up to 85% at 1 bar. In the FO process, the membranes can achieve water flux of 17 and 12 l/m2.h for the AL-DS and AL-FW configurations, respectively, using a 2000 ppm Na¬2SO4 aqueous solution as the feed and 0.5 M Na2SO4 as the draw solution. When the feed contained 1000 ppm bovine serum albumin (BSA) and 2000 ppm Na2SO4, a steady water flux of 11 l/m2.h can be maintained using 0.5 M Na2SO4 as the draw solution at ambient temperature of 23 °C. The approach of making FO membranes developed in this study offers the advantages of simple fabrication process, tailorable selective layer and promising membrane performance for protein-contained wastewater treatment by FO process.